DINAMIKA MENGELOLA JEMAAT POTENSIAL: STUDI KASUS PEMBERDAYAAN WARGA GEREJA OLEH PARA GEMBALA SIDANG DI GBIS - David Eko Setiawan; Hani Rohayani (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2023)
The dynamics of potential church member empowerment by Pastors in the Bethel Injil Sepenuh Church (GBIS) community are described in this article. Through a descriptive quantitative study using surveys and descriptive percentage analysis, this research explores how GBIS Pastors manage potential church members in their services. The findings indicate that the management of potential church members in GBIS has a unique dynamic, shaped by the perceptions of 81 GBIS Pastor respondents. The results of this research provide valuable insights for GBIS Pastors and church synods to enhance their management of potential church members and ensure equitable and effective access to church services.